Immunoproteomics and immunoinformatics analysis of Cryptococcus gattii: novel candidate antigens for diagnosis. (April 2013) - Martins, Liline Maria Soares; Andrade, Hélida Monteiro de; Vainstein, Marilene Henning; Wanke, Bodo; Schrank, Augusto; Balaguez, Claudia Bemfica; Santos, Patrícia Ribeiro dos; Santi, Lucélia; Pires, Simone da Fonseca; da Silva, Adalberto Socorro; de Castro, José Adail Fonseca; Brandão, Rafael Melo Santos de Serpa; et al.
Aim: To identify immunoreactive proteins of Cryptococcus gattii genotype VGII and their B-cell epitopes.Materials & methods: We combined 2D gel electrophoresis, immunoblotting and mass spectrometry to identify immunoreactive proteins from four strains of C. gattii genotype VGII (CG01, CG02, CG03 and R265). Next, we screened the identified proteins to map B-cell epitopes.Results: Sixty-eight immunoreactive proteins were identified. The strains and the number of proteins we found were: CG01 (12), CG02 (12), CG03 (18) and R265 (26). In addition, we mapped 374 peptides potentially targeted by B cells.Conclusion: Both immunoreactive proteins and B-cell epitopes of C. gattii genotype VGII that were potentially targeted by a host humoral response were identified. Considering the evolutionary relevance of the identified proteins, we may speculate that they could be used as the initial targets for recombinant protein and peptide synthesis aimed at the development of immunodiagnostic tools for cryptococcosis.